Redox Equilibria of Glass Melts with Gas Phase and Specific Resistivities of Quenched Glasses in the Systems Fe2O3-RP2O6 and TiO2 - HASHIMOTO, Tadahiro; ARAI, Kazumasa; YOSHIDA, Tetsuro; OKADA, Yuji (Journal of the Ceramic Association, Japan, 1973)
Redox equilibria of glass melts with oxygen and CO2-CO mixtures containing oxygen partial pressures from 100 to 10-14 atm were studied. The structure-sensitive properties of quenched glasses such as specific resistivity, were found to be correlated to the redox equilibrium. In the glass melts of 5Fe2O3⋅95RP2O6 and 7TiO2⋅93RP2O6, the concentration ratios [Fe2+]/[Fe3+] and [Ti3+]/[Ti4+] were the highest for the lowest basicity (R=Mg), decreasing in the order of Mg, Ca, Ba (O-type), while concentrations of high-valent ions (Fe3+, Ti4+) remained nearly unchanged and those of low-valent ions (Fe2+, Ti3+) decreased. On the other hand, in the glass melts containing larger amounts of Fe2O3 such as 20Fe2O3⋅80RP2O6, the ratio [Fe2+]/[Fe3+] increased with increasing basicity (R-type). At high oxygen partial pressures, ferric ion concentration remained nearly unchanged and ferrous ion increased with increasing basicity. At low oxygen partial pressures ferrics ion decreased and ferrous ion concentration remained nearly unchanged. The specific resistivities of the quenched glasses of 7TiO2⋅93RP2O6 and 20Fe2O3⋅80RP2O6, which were obtained from the melts in redox equilibria, decreased with increasing basicity by replacing R with Mg, Ca, Ba. A minimum of specific resistivity was observed when the concentration ratio of low to high valent ions of transition metal was approximately equal to unity. However, this ratio decreased for the glasses of 7TiO2⋅93RP2O6 and increased slightly for 20Fe2O3⋅80RP2O6 as the basicity increased. TiO2 was more effective than Fe2O3 on the lowering of specific resistivity. It is concluded from these experimental results that the redox equilibria in the melts of 5Fe2O3⋅95RP2O6 and 7TiO2⋅93RP2O6 are expressed as, 2[XOx](2x-n-m)-=2Xn++(2x-m)O2-+m/2 O2 where X is Fe or Ti and m=1. Complex oxiacid ions Fe2O54- or TiO44- seemed to be involved in the equilibria. In the melts of 20Fe2O3⋅80RP2O6, equilibrium is expressed as, 2[XOx](2x-n-m)-+(m-2(x-y))O2-=2[XOy](2y-n)-+m/2 O2 The oxygen ion coordination number of the ferrous complex ion has not been found in the present work.